Synthesis and nonlinear optical effects of alpha-methylstyrene copolymers bearing the pyridinium and quinolinium salt chromophore - Choi, DH; Ahn, JS; Kim, N (POLYMER SOC KOREA, 1997)
We synthesized alpha-methylstyrene copolymers bearing the two different organic salt type chromophores and investigated their second-order nonlinear optical properties using the linear electro-optic(EO) coefficient measurement and second harmonic generation (SHG). In the synthesis of copolymers, N-vinylcarbazole or p-hydroxyphenylmaleimide were employed as a comonomer. In the synthesis of organic salt type chromophore, pyridinium and quinolinium were selected as cationic species and tetraphenylboron was selected as a counterion. In the case of p-hydroxyphenylmaleimide copolymer, we made an attempt to induce thermal crosslinking reaction utilizing diisocyanate. Crosslinking reaction via tetramethylene-m-xylidene diisocyanate was traced by virtue of infrared spectroscopy. The stability of second-order nonlinear optic property was also observed.
Keywords: 2ND-HARMONIC GENERATION